2018
DOI: 10.1371/journal.ppat.1006876
|View full text |Cite
|
Sign up to set email alerts
|

The novel antibiotic rhodomyrtone traps membrane proteins in vesicles with increased fluidity

Abstract: The acylphloroglucinol rhodomyrtone is a promising new antibiotic isolated from the rose myrtle Rhodomyrtus tomentosa, a plant used in Asian traditional medicine. While many studies have demonstrated its antibacterial potential in a variety of clinical applications, very little is known about the mechanism of action of rhodomyrtone. Preceding studies have been focused on intracellular targets, but no specific intracellular protein could be confirmed as main target. Using live cell, high-resolution, and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 78 publications
(144 reference statements)
7
102
0
3
Order By: Relevance
“…S9). Consistent with these data, a recent study reported that the antibiotic agent rhodomyrtone causes increased membrane fluidity in Bacillus subtilis and kills its persister cells (23).…”
Section: The Killing Of Mrsa Persisters Is Correlated With Increased supporting
confidence: 55%
See 1 more Smart Citation
“…S9). Consistent with these data, a recent study reported that the antibiotic agent rhodomyrtone causes increased membrane fluidity in Bacillus subtilis and kills its persister cells (23).…”
Section: The Killing Of Mrsa Persisters Is Correlated With Increased supporting
confidence: 55%
“…Insertion of particular membrane disrupting compounds into lipid bilayers is known to cause dramatic changes in membrane fluidity that disrupts the normal liquid-crystalline phase of the membrane (21)(22)(23). This results in passive permeabilization, loss of membrane protein functions, leakage of cellular components, and bacterial death (24).…”
Section: Bithionol Interacts With and Disrupts The Bacterial Mimetic mentioning
confidence: 99%
“…This phenomenon could also be applied to rhodomyrtone treatment in S. suis as the dramatic reduction in cell number was seen only after 4 hours at the highest concentration of rhodomyrtone treatment and this duration was extended in dosedependent manners. These might due to the combinatorial effects of rhodomyrtone on nucleoid segregation and loss of function of other proteins trapped in RIF (Saeloh et al 2018). Therefore, the additional functional consequence of rhodomyrtone treatment on other protein which directly or indirectly involved in the nucleoid segregation remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Saeloh et al (2018) demonstrated that rhodomyrtone caused delocalization of membrane proteins correlated to the cell size and shape defects in B. subtilis and S. aureus (Saising et al 2018;Sianglum et al 2018). Two important cell division proteins, DivIVA and FtsA were known to associate with FtsZ during the septum formation as a nal step of cell division.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation